2015
DOI: 10.1021/acs.cgd.5b01034
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Inclusion of Wheel-and-Axle Diol Hosts Featuring Benzo[b]thiophene Units as a Lateral Construction Element

Abstract: By applying the 'wheel-and-axle' host concept and incorporating a previously developed heteroaromatic substitution strategy, a new type of diol hosts featuring two di(benzo [b]thien-2-yl)hydroxymethyl units attached to both ends of a central ethynylene (3) and 1,4-phenylene (4) moiety is reported. The syntheses of the host compounds are described and solvent inclusion formation via crystallization has extensively been studied showing a remarkable inclusion capability of the compounds. X-ray diffraction analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Furthermore, decoration of the host with functional groups capable of hydrogen bonding often improves the inclusion properties. Wheel‐and‐axle molecular geometries (Figure ), first reported by Toda, correspond to this line of reasoning , . Such molecular geometries are produced by connecting two bulky propeller‐shaped groups by a long linker (for short linkers, they are known as the dumbbell[2a] type).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, decoration of the host with functional groups capable of hydrogen bonding often improves the inclusion properties. Wheel‐and‐axle molecular geometries (Figure ), first reported by Toda, correspond to this line of reasoning , . Such molecular geometries are produced by connecting two bulky propeller‐shaped groups by a long linker (for short linkers, they are known as the dumbbell[2a] type).…”
Section: Introductionsupporting
confidence: 54%
“…Wheel-and-axle molecular geometries (Figure 1), first reported by Toda,[4] correspond to this line of reasoning. [3,5] Such molecular geometries are produced by connecting two bulky propeller-shaped groups by a long linker (for short linkers, they are known as the dumbbell [2a] type). These types of compounds have been developed into a large family of purely organicbased hosts for lattice-inclusion compounds with variations in the end groups (wheels) and/or central linear building block (axle).…”
Section: Introductionmentioning
confidence: 99%
“…This would mean that the hosts featuring an ethynylene unit attached to the hydroxyl substituted carbon atom (BTh1, 2, 4-6) are favored over hosts having an attached phenylene unit (BTh2, 1, 3); but also in this respect there is no corresponding trend justified by the data. Hence, the results once more [12,13,36] In further studies, we observed a preconditioning effect of the sorptive coating. This has been found working with host compound 6 showing high ratios of included EtOH both on solvent crystallization (1:4 stoichiometry) and vapor sorption (185 %) when 6 having been deposited from CHCl3 solution.…”
Section: Solvent Vapor Absorption Behaviormentioning
confidence: 52%
“…1) leads to a distinct enhancement of the crystalline inclusion formation with organic solvent molecules [13]. Following this line of thought, the question arises whether the intended homologues of BTh1 and BTh2, i.e.…”
Section: Capability Of Inclusion Formationmentioning
confidence: 99%
See 1 more Smart Citation